A segmented pressure-controlled diffusion heat treatment method for chemical vapor silicon-aluminizing of a high-temperature alloy turbine blade

CN122959646APending Publication Date: 2026-10-23ZHUZHOU RUIDEER METALLURGICAL EQUIP MFG CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202611418581.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-09-14
Publication Date
2026-10-23

AI Technical Summary

Technical Problem

然而,现有工艺大多关注涂层的形成与冷却效率,对渗层形成后的扩散热处理及应力调控关注不足,渗层中残余应力分布不均、涂层与基体结合强度不足的问题仍较为突出

Benefits of technology

1、双金属夹具利用两种材料的热膨胀差自动产生根部压应力,无需外部施力机构,炉壁不存在旋转轴穿透件,避免了动密封磨损和泄漏对真空环境的破坏,使炉内始终维持高真空度,从而保证扩散热处理过程中涂层表面无氧化,涂层与基体之间的冶金结合不受氧化层阻碍。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122959646A_ABST
    Figure CN122959646A_ABST
Patent Text Reader

Abstract

The application provides a segmented pressure control diffusion heat treatment method for chemical vapor silicon-containing aluminizing of a high-temperature alloy turbine blade, and belongs to the technical field of high-temperature alloy heat treatment and diffusion coating. The application forms a silicon-containing aluminizing preformed layer on the blade through chemical vapor deposition, clamps the blade and then puts the blade into a multi-zone vacuum furnace, generates a root pressure stress by utilizing the bimetallic thermal expansion difference when the blade is heated, promotes element diffusion by segmenting the pressure and keeping warm, then cools the blade by a first temperature difference so that the tip is higher than the root, and when the average temperature T avg of the blade is T avg = 460 DEG C, switches the mechanical contact hard wire to a second temperature difference so that the root is higher than the tip, continues to cool, switches to a third temperature difference so that the tip is higher than the root and keeps the state, then stops heating, removes the ladder, fills argon to keep pressure, closes the furnace door to cool to 80 DEG C, and takes out the blade, thereby completing the heat treatment of the blade. The application solves the technical problems of easy leakage and failure of rotary dynamic sealing, and coating cracking caused by uncontrollable thermal stress in the cooling stage.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of high-temperature alloy heat treatment and diffusion coating technology, and mainly to a segmented pressure-controlled diffusion heat treatment method for high-temperature alloy turbine blades using chemical vapor deposition of silicon-containing aluminizing. Background Technology

[0002] Aluminum silicide coatings are an important means to improve the high-temperature oxidation resistance of turbine blades, and various preparation methods such as vapor-phase aluminizing and slurry aluminizing are currently available. However, most existing processes focus on coating formation and cooling efficiency, while paying insufficient attention to diffusion heat treatment and stress control after coating formation. The problems of uneven residual stress distribution in the coating and insufficient bonding strength between the coating and the substrate remain prominent.

[0003] To address the aforementioned issues, CN117890173B discloses a method for preparing a metallographic image of a nickel-based superalloy turbine blade with a protective aluminum-silicon coating. This method protects the hard and brittle aluminum-silicon coating by electroplating a nickel layer, thus preventing coating cracking and peeling during metallographic preparation. However, since it relies on physical isolation to prevent damage to the coating during sample preparation rather than controlling the quality of the diffusion layer itself, it only affects the metallographic sample preparation stage and cannot improve the inherent brittleness and residual stress of the diffusion layer. Therefore, it is a post-processing protection method rather than a process optimization. CN122189558A discloses a vapor-phase aluminizing method for nickel-based single-crystal superalloy turbine blades. This method accelerates the cooling rate and reduces thermal stress through stepped gas cooling. While it addresses thermal stress control during the cooling stage, the cooling process still relies primarily on a single cooling path and fails to guide the stress distribution of the diffusion layer by actively controlling the temperature difference direction. Furthermore, it does not address the optimization of elemental distribution and phase composition through post-diffusion heat treatment processes.

[0004] In summary, existing technologies lack a systematic method for actively controlling residual stress, optimizing elemental distribution, and improving the bonding strength between the coating and the substrate through a controllable diffusion heat treatment process after the diffusion layer has formed. Therefore, there is an urgent need to develop a segmented pressure-controlled diffusion heat treatment method for chemical vapor deposition of silicon-containing aluminate in high-temperature alloy turbine blades. This method would achieve proactive control of the diffusion layer quality throughout the entire process through segmented pressure control, temperature reversal, and step-by-step unloading. Summary of the Invention

[0005] To address the shortcomings of existing technologies, this invention proposes a segmented pressure-controlled diffusion heat treatment method for high-temperature alloy turbine blades using chemical vapor deposition (CVD) to form a silicon-aluminized pre-layer. After clamping, the blade is placed in a multi-zone vacuum furnace. During heating, the bimetallic thermal expansion difference generates compressive stress at the root. Segmented pressure increase and heat preservation promote element diffusion. Subsequently, cooling is applied using a first temperature difference to ensure the blade tip is higher than the blade root. When the average blade temperature T... avg Upon entering the window, the guide rail is initially pushed in, switching from mechanical contact to a second temperature difference that raises the leaf root above the leaf tip, and the temperature continues to drop to T.avg After reaching 460℃, the temperature is switched to the third temperature difference to keep the blade tip higher than the blade root. Then, the heating is stopped, the ladder is removed, argon is charged and pressure is maintained, the furnace door is closed, and the part is taken out after cooling to 80℃. This completes the heat treatment of the blade, which can be used in the fields of high-pressure turbine blades for aero engines, hot-end components of industrial heavy gas turbines, and guide blades for marine gas turbines.

[0006] This invention proposes a segmented pressure-controlled diffusion heat treatment method for high-temperature alloy turbine blades using chemical vapor deposition with silicon-containing aluminizing. The specific technical solution is as follows: Step 1: Clean the nickel-based high-temperature alloy turbine blades and confirm the air circulation of the film pores. Cover the non-permeable parts with an alumina sleeve. After loading into the vapor deposition furnace, first pass an AlCl3-containing first reaction gas for aluminization deposition under a protective atmosphere, and then pass a SiCl4-containing second reaction gas for silicon deposition. The reaction tail gas is treated by alkaline absorption and a leakage interlock is set. After the deposition is completed, switch to argon purging and cooling to obtain a blade with a silicon-aluminate pre-layer on the surface.

[0007] Step 2: Using an alumina insulating pad, the root of the blade with the pre-formed layer is inserted into a bimetallic thermal expansion locking fixture, clamping only the blade root and keeping the blade body and tip free. The product blade and the control blade with temperature measuring points at the blade root, blade middle, and blade tip are placed together in a multi-zone heating vacuum furnace. The furnace has 6 independent heating zones along the blade height. After evacuation, the furnace pressure is controlled sequentially in the low-pressure vacuum zone, the 50Pa medium-pressure zone, and the 500Pa high-pressure zone, and the temperature is raised to the corresponding diffusion temperature and then held at that temperature. During the holding period, the output of each zone is continuously adjusted according to the measured temperature of the three measuring points of the control blade to keep the blade tip temperature higher than that of the blade root.

[0008] Step 3: After the heat preservation is completed, adjust the furnace pressure to the cooling pressure, reduce the set temperature of the independent heating zone at the preset cooling rate, and keep the actual temperature of the blade tip higher than the actual temperature of the blade root. When the average temperature of the blade enters the first reversal temperature window, smoothly reverse the axial temperature difference direction within 5 minutes so that the actual temperature of the blade root is higher than the actual temperature of the blade tip.

[0009] Step 4: Continue cooling while keeping the measured temperature at the leaf root higher than that at the leaf tip. During the cooling process, continuously adjust the output of each heating zone based on the measured temperatures at the leaf root, leaf middle, and leaf tip to maintain a constant axial temperature difference until the average temperature of the blade drops to the preset end temperature.

[0010] Step 5: When the average temperature of the blade drops to the second reversal temperature window, within 5 minutes, smoothly reverse the axial temperature difference direction from the blade root being higher than the blade tip to the blade tip being higher than the blade root, and maintain this for a preset time. Then, gradually reduce the temperature difference to zero and stop heating. At the same time, argon gas is introduced to maintain the furnace pressure. The furnace door is kept closed until the blade temperature drops below the set temperature, after which the furnace door is opened and the blade is removed.

[0011] Compared with the prior art, the beneficial effects of the present invention are as follows: 1. The bimetallic clamp automatically generates root compressive stress by utilizing the thermal expansion difference between the two materials. No external force application mechanism is required. There are no rotating shaft penetration parts in the furnace wall, which avoids the damage to the vacuum environment caused by dynamic seal wear and leakage. This ensures that the vacuum level inside the furnace is always maintained, thereby ensuring that the coating surface is free from oxidation during the diffusion heat treatment process and that the metallurgical bond between the coating and the substrate is not hindered by the oxide layer.

[0012] 2. The two temperature reversals change the dominant direction of longitudinal thermal shrinkage stress twice, avoiding the continuous accumulation of stress in the same area under a single temperature difference. This makes the residual stress distribution inside the coating more uniform, and the coating is less likely to develop cracks due to stress concentration during subsequent service, thus extending its thermal fatigue life.

[0013] 3. The initial push into the guide rail is triggered when the average temperature of the blades enters the preset reversal temperature window. After the window is reached, the push rod displacement directly switches the temperature control setting value through mechanical contact hard wire. The switching action does not rely on the PLC timer or external communication signal, avoiding clock deviation and signal transmission delay between multiple control links. This ensures that the temperature difference reversal action starts at the same measured temperature node in each batch, guaranteeing the consistency of coating stress and thickness distribution between batches.

[0014] 4. The reverse-sequence layered unloading is performed in the order of coil disconnection, temperature difference reversal, and gradient removal, with relaxation intervals between each action. This avoids stress abrupt changes caused by the simultaneous removal of multiple field quantities, resulting in a smooth stress transition at the interface between the coating and the substrate. This improves the interfacial bonding strength and makes the coating less prone to peeling during thermal cycling. Attached Figure Description

[0015] Figure 1 The images show cross-sectional topography of the sample from Example 1, where a is the topography of the leaf root, b is the topography of the leaf midsection, and c is the topography of the leaf tip. Figure 2 This is a gradient distribution diagram of the elements in the cross-section of the sample from Example 1. Figure 3 The XRD diffraction patterns are for the examples and comparative samples. Detailed Implementation

[0016] The technical solutions in the embodiments of the present invention will be clearly and completely described below. Obviously, the described embodiments are only a part of the embodiments of the present invention, and not all of them. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.

[0017] This invention proposes a segmented pressure-controlled diffusion heat treatment method for high-temperature alloy turbine blades using chemical vapor deposition with silicon-containing aluminizing. The specific technical solution is as follows: 1. Precast layer deposition In a chemical vapor deposition (CVD) furnace, aluminum and silicon sources are sequentially introduced to form a silicon-aluminate deposition layer on the blade surface. The CVD process utilizes a gaseous precursor to undergo a heterogeneous reaction on the heated blade surface, generating a solid deposition layer. Aluminum and silicon source gases are sequentially introduced into the reaction chamber, where active aluminum and silicon atoms are released on the blade surface through reduction or thermal decomposition reactions. The formation of the deposition layer is controlled by surface reaction kinetics and diffusion mass transfer. The blade temperature is maintained in the intermediate temperature range to ensure a balance between the deposition rate and the coating density. Aluminum preferentially nucleates on the surface and grows into a continuous layer, while silicon atoms enter the aluminate lattice through substitution or interstitial means or form discrete silicon-rich phases, creating a compositional gradient with gradually increasing silicon content in the outer layer.

[0018] At the deposition temperature, the two elements exhibit a certain degree of interdiffusion capability, and preliminary element redistribution begins during the deposition stage, forming an initial compositional gradient with a silicon-rich outer layer and a silicon-poor inner layer. This gradient dominates the migration direction of the elements during subsequent diffusion processes, causing more silicon to remain on the outer side while aluminum continues to be supplied inward. After deposition, a gas shut-off purging process replaces residual precursors and byproducts with inert gas to avoid unnecessary surface reactions during cooling.

[0019] 2. Clamping and diffusion insulation After the blade root with the deposited layer is locked into a bimetallic clamp, it is placed in a multi-zone vacuum furnace, where it is heated and held at room temperature after staged pressurization. The bimetallic clamp consists of two metal components with different coefficients of linear expansion. During heating, the difference in thermal elongation between the frame and the tie rod is absorbed by the elastic load-limiting part and converted into continuous compressive stress acting on the blade root contact surface. This stress gradually increases with temperature and remains stable within the diffusion temperature range. Moreover, the compressive stress only acts on the blade root, while the blade body and tip are not subjected to clamping force, thus avoiding the introduction of additional thermal stress to the main blade structure by rigid contact. During cooling, the clamp automatically reduces the compressive stress as the temperature decreases, thereby achieving natural unloading.

[0020] The furnace is evacuated to remove oxygen and moisture, eliminating the risk of high-temperature oxidation. The furnace pressure is then increased sequentially: the low-pressure stage removes adsorbed gases and residual volatiles; the medium-pressure stage improves furnace temperature uniformity by increasing gas thermal conductivity and convective heat transfer efficiency; and the high-pressure stage utilizes the higher gas heat capacity and thermal conductivity to achieve sufficient thermal equilibrium between the blades and the furnace. Once the furnace temperature reaches the diffusion temperature, the chemical potential gradient between the coating and the substrate drives aluminum to diffuse into the substrate, while nickel and cobalt in the substrate diffuse outwards into the coating, forming interdiffusion couples. The β-NiAl phase continues to grow and stabilize inside the coating. During the heat preservation period, the output of each heating zone is continuously adjusted based on the measured temperatures at the blade root, middle, and tip, ensuring the blade tip temperature is higher than the blade root temperature. The difference in diffusion coefficients at different heights is used to pre-establish the longitudinal thickness variation trend, separating thickness control from stress control in the subsequent cooling stage.

[0021] 3. First temperature difference reversal After the heat preservation is completed, the pressure is reduced and the temperature is controlled according to the first temperature distribution. When the average blade temperature T avg Upon reaching the first reversal temperature window, the guide rail is pushed in and the second temperature distribution is switched. During cooling, the longitudinal temperature gradient causes differences in the cooling rate and cooling amplitude at different heights of the blade, resulting in changes in the amplitude of transient thermal strain at each location and the distribution of shear stress and normal stress at the coating / substrate interface. At this time, the first temperature distribution causes the blade tip temperature to be higher than the blade root temperature, i.e., ΔT1 = T. 尖 -T 根 >0, during the cooling process, the temperature drop in the leaf root region is greater than that in the leaf tip region, the change in thermal strain on the leaf root side is greater, and the differential thermal strain shows a positive gradient distribution along the longitudinal direction.

[0022] When T avg After entering the inversion window, the second temperature distribution is switched, the longitudinal temperature difference direction is reversed, and the sign of the differential thermal strain changes accordingly. At this time, the temperature drop in the blade tip region is greater than that in the blade root region, i.e., ΔT2 = T. 根 -T 尖 When the differential thermal strain gradient is greater than 0, the direction of the differential thermal strain gradient reverses, and the interfacial stress distribution is adjusted in the opposite direction. This change in the sign of the differential thermal strain causes the accumulated interfacial shear stress to redistribute during the reversal process, and some of the accumulated strain energy is released and re-accumulated from the new differential thermal strain starting point.

[0023] The switching time is chosen within the temperature range where the material still possesses a certain degree of creep relaxation capability, allowing the interfacial stress to be effectively adjusted through microscopic deformation after the sign of the differential thermal strain changes. After the switching is completed, T... avg As the temperature continues to decrease, the longitudinal temperature difference direction is opposite to that before the switch, and the sign of the differential thermal strain continues to reverse, causing the stress accumulation path at the interface between the coating and the substrate to enter a new state.

[0024] 4. Reverse gradient cooling While maintaining the second temperature distribution, cooling continues until the average blade temperature drops to the preset end temperature. During the reverse gradient cooling stage, the blade continuously experiences a reverse longitudinal temperature difference along its height, with the cooling rate at each height remaining constant. As the material's yield strength gradually increases and its creep relaxation capability continuously weakens during cooling, fluctuations in the temperature difference during cooling will cause asynchronous changes in the shrinkage rate at each height. The accumulated differential thermal strain will be superimposed with additional transient thermal strain components, resulting in uncontrollable transient thermal shocks at different height sections.

[0025] The controller continuously corrects the output of each heating zone based on the measured temperature at three points: the root, middle, and tip of the blade. This ensures that the axial temperature difference remains at the target value throughout the cooling process, preventing asynchronous changes in the contraction rate at different heights caused by temperature fluctuations. It also ensures that the differential thermal strain accumulates gradually in the opposite direction at a predetermined rate, guaranteeing a smooth transition from the cooling process to the subsequent stress control stage.

[0026] 5. Second temperature difference reversal and unloading When the average leaf temperature enters the second reversal temperature window, the temperature difference direction is reversed from leaf root being higher than leaf tip to leaf tip being higher than leaf root and maintained for a preset time. At this time, ΔT3 = T. 尖 -T 根 >0, then gradually reduce the temperature difference to zero and stop heating. Remove the part after cooling. When entering the first, second, and third temperature distributions, the set value of each heating zone should be adjusted according to T. avg The cooling curve decreases synchronously, and the controller applies only the necessary bias to each zone to keep the measured ΔT at the target value. Furthermore, all temperature reversals occur under mild conditions, making the temperature change a gradual process and avoiding localized thermal shock caused by sudden jumps. After cooling to the low-temperature range, the material loses its plastic deformation capacity, and the resulting stress state will remain fixed until room temperature. If the temperature difference direction is not adjusted further, the previously accumulated stress state will remain unchanged. The second reversal readjusts the contraction sequence of each blade segment by changing the temperature difference direction. In the final stage before the material loses its deformability, the stress direction is actively intervened, causing a controllable change in the stress direction, which is then fixed.

[0027] The unloading phase is executed in steps. After adjusting the temperature difference direction, a preset time is maintained to allow for sufficient stress redistribution. Subsequently, the temperature difference is gradually reduced to zero and heating is stopped to prevent simultaneous temperature reversal and disappearance of the thermal gradient. Argon gas is introduced to maintain furnace pressure while heating is stopped, and the furnace door remains closed until the blade temperature drops below 80°C before opening to prevent thermal shock from high-temperature removal. After cooling to room temperature, the bimetallic clamp automatically reduces compressive stress due to the temperature drop and removes the blade, thus completing the blade processing.

[0028] The following are specific embodiments and comparative examples of the present invention, which are used to more specifically demonstrate the segmented pressure-controlled diffusion heat treatment method for high-temperature alloy turbine blades by chemical vapor phase silicon-containing aluminizing provided by the present invention.

[0029] Example 1 S1: Place the DD6 single-crystal nickel-based high-temperature alloy turbine blade and a control blade in acetone and ultrasonically clean them for 10 minutes at 30℃ and 40kHz. After removing them, blow dry the surface with high-purity nitrogen. Then clean them in anhydrous ethanol for 10 minutes under the same conditions. After that, blow dry the surface with high-purity nitrogen until completely dry. Check the ventilation of the air film pores of the main blade and the control blade, and cover their roots with alumina covers. Put the treated and covered blades into the vapor deposition furnace. After closing the furnace door, start the vacuum pump to evacuate the furnace to 1Pa. Then fill it with high-purity argon to atmospheric pressure and evacuate it to 1Pa again. Repeat this operation 3 times to completely remove the air in the furnace. The AlCl3 generator temperature was controlled at 130℃, and the SiCl4 generator temperature was maintained at 35℃ using a constant temperature water bath. The AlCl3 steam delivery pipeline was insulated at 250℃ throughout to prevent condensation. The total deposition pressure was controlled at 200Pa (aluminide deposition) and 150Pa (silicon deposition), the AlCl3 partial pressure was 16Pa (aluminide deposition) and 6Pa (silicon deposition), and the SiCl4 partial pressure was 3Pa. The reaction gas flow rate was set by a mass flow controller. The AlCl3 steam flow rate was calibrated by combining the generator outlet pressure with the carrier gas flow rate and converted to an equivalent standard flow rate. The reaction tail gas was absorbed and treated by a 10wt% NaOH solution before being discharged. Online HCl concentration detection and leakage interlock alarm devices were installed at the furnace exhaust port and the inlet and outlet of the scrubber. If the HCl concentration exceeded the standard... The system automatically cuts off the supply of reaction gas and starts emergency exhaust. After the replacement is completed, argon is introduced into the furnace to atmospheric pressure, and the temperature is raised to 950°C at 3°C / min and held for 10 min. After the holding period, the first reaction gas with a volume ratio of AlCl3 and H2 of 8:92 is introduced into the furnace at a flow rate of 180 L / h and continues to be introduced for 3 h to complete the aluminization deposition. Then the first reaction gas is cut off and heating is stopped. When the furnace temperature drops to 880°C, it is held for 5 min. Then the second reaction gas with a volume ratio of AlCl3, SiCl4 and H2 of 4:2:94 is introduced into the furnace at a flow rate of 180 L / h and continues to be introduced for 1 h to complete the silicon deposition. After the deposition is completed, the second reaction gas is cut off and the furnace is purged with pure argon at a flow rate of 200 L / h for 30 min to remove the residual reaction gas. After purging, heating was stopped, and the argon flow rate was reduced to 50 L / h to maintain a slight positive pressure inside the furnace. The furnace was then cooled to room temperature at a rate of 2 °C / min. Subsequently, the furnace door was opened and the DD6 blade and the control blade were removed to obtain a turbine blade with a silicon-aluminate preform layer formed on its surface.

[0030] S2: Vacuum-compatible temperature sensors are fixed at the root, middle, and tip of the product blade and the control blade, respectively. The average temperature of the root, middle, and tip of the blade is taken as the average temperature T of the entire blade. avg That is, T avg=(Troot + Tmiddle + Ttip) / 3. The blade root obtained in S1 is fitted into a bimetallic thermal expansion locking clamp. This clamp consists of a HAYNES 230 alloy frame and a TZM molybdenum alloy tie rod, with an effective thermal deformation length of 120mm and a room temperature assembly gap of 0.25mm. The frame is equipped with an elastic load-limiting beam with an equivalent stiffness of 2.8kN / mm. At 1020℃, the compressive stress on the blade root contact surface is 11.0±1.0Mpa. A 1mm thick alumina isolation pad is placed on each side of the blade root. After the blade root is installed, only the blade root is clamped, leaving the blade body and tip completely free. The clamp is set to maintain only the initial mechanical contact state without additional clamping force. The clamped blade, along with the clamp, is placed into a multi-zone heating vacuum furnace. The furnace is divided into six independent heating zones along the blade height, designated as zones 1 to 6 from blade root to blade tip. After closing the furnace door, the vacuum pump is activated to evacuate the furnace to below 1 Pa. Then, while maintaining the vacuum, the temperature is increased from room temperature to 600°C at a rate of 2°C / min as the low-pressure zone. Evacuation is then stopped, and high-purity argon is introduced to raise the furnace pressure to 50 Pa as the medium-pressure zone. Once the furnace pressure stabilizes, the temperature is increased to 900°C at a rate of 2°C / min. Argon is then introduced to raise the furnace pressure to 500 Pa as the high-pressure zone, and the temperature is further increased to T at a rate of 1°C / min. avg =1020℃ for diffusion insulation. During the insulation period, the controller continuously adjusts the output of the six heating zones according to the measured temperature of T root, T middle and T tip, so that the measured blade tip temperature is kept 25±3℃ higher than the blade root. The insulation is carried out for 3 hours, and the temperature of each measuring point and the output power of each zone are recorded.

[0031] S3: After the heat preservation is completed, the furnace pressure is reduced to 120 Pa at a rate of 10 Pa / min. Simultaneously with the pressure reduction, the reference setpoints for each heating zone are adjusted at a rate of 2 °C / min according to T. avg Simultaneously decreasing, the controller maintains the measured blade tip temperature 35±3℃ higher than the blade root temperature, i.e., the first temperature distribution, when T avg When the temperature drops to 825℃, the guide rail carrying the control blade is pushed into the furnace by a welded metal bellows pusher rod. The pushing stroke is 300mm. When the guide rail reaches the end of the pushing stroke, the mechanical position contact is triggered for the first time. The temperature difference reversal is initiated. Within 5 minutes after the guide rail is triggered, the controller gradually transitions the measured temperature difference from 35±3℃ higher at the blade tip than at the blade root to 35±3℃ higher at the blade root than at the blade tip. The set values ​​of each zone change continuously during the transition without abrupt switching. After the reversal is completed, the blade root temperature is maintained at 35±3℃ higher than the blade tip, i.e., the second temperature distribution. Subsequently, the temperature continues to decrease at a rate of 2℃ / min. avg .

[0032] S4: Continue to decrease T at a rate of 2℃ / min while maintaining the second temperature distribution. avgThe control system continuously adjusts the output of the six heating zones based on the measured temperatures of the leaf root, leaf middle, and leaf tip, ensuring that the measured leaf root temperature is maintained 35±3℃ higher than the leaf tip temperature, until T... avg The process ends when the temperature drops to 460℃.

[0033] S5: When the temperature drops to 460℃, the measured temperature difference is gradually and smoothly reversed within 5 minutes from the blade root temperature being 35±3℃ higher than the blade tip temperature to the blade tip temperature being 20±3℃ higher than the blade root temperature, i.e., the third temperature distribution. No instantaneous jumps are made during the reversal, and the third temperature distribution is maintained for 8 minutes. Then, the temperature difference between the blade tip and the blade root is gradually reduced to 0℃ within 5 minutes. Then, multi-zone heating is stopped, and high-purity argon gas is introduced into the furnace at a flow rate of 80L / h. When the pressure inside the furnace rises to 800Pa, the argon gas flow rate is reduced to 30L / h to maintain this pressure. The furnace door is kept closed, and the clamps automatically reduce their clamping force inside the furnace as the temperature drops. After cooling continues until the product blade temperature is no higher than 80℃, the furnace door is opened, the blade is removed using graphite pliers, and it is further cooled to room temperature before being taken out, thus obtaining the processed turbine blade.

[0034] The prepared turbine blades contain the following proportions of chemical elements: Co 8.50%~9.50%, Cr 3.80%~4.80%, W 7.00%~9.00%, Mo 1.50%~2.50%, Al 6.10%~6.40%, Ta 6.00%~7.00%, Re 1.80%~2.50%, Si 0.30%~0.50%, C≤0.04%, Fe≤0.20%, Mn≤0.15%, Zr≤0.10%, P≤0.018%, S≤0.001%, with the balance being Ni and unavoidable impurities.

[0035] Example 2 The preparation method according to Example 1 differs in that: S1: Cleaning temperature 25℃, AlCl3 accounts for 6% of the volume of the first reaction gas in the aluminization deposition, the first reaction gas flow rate is 160L / h, the aluminization deposition temperature is 930℃, and the deposition time is 2.5h; SiCl4 accounts for 1% of the volume of the second reaction gas in the silicon deposition, the silicon deposition temperature is 865℃, and the deposition time is 0.8h. S2: The furnace temperature in the low-pressure section is 580℃, the furnace temperature in the medium-pressure section is 860℃, the furnace temperature in the high-pressure section is 1000℃, and the diffusion heat preservation time is 2.5h; S3: The pressure reduction rate is 8Pa / min, the furnace pressure is reduced to 100Pa, the average temperature of the blades when they are pushed into the guide rail is 800℃, and the cooling rate is 1℃ / min. S4: The cooling rate is 1℃ / min, and the average blade temperature at the end of cooling is 450℃. S5: Maintain the third temperature distribution time for 5 minutes, the argon flow rate after heating is stopped is 60 L / h, the furnace pressure is maintained at 700 Pa, the argon flow rate when maintaining the pressure is 25 L / h, and the rest of the steps are the same.

[0036] The prepared turbine blades contain the following chemical elements in the following proportions: Co 8.50%~9.50%, Cr 3.80%~4.80%, W 7.00%~9.00%, Mo 1.50%~2.50%, Al 5.90%~6.10%, Ta 6.00%~7.00%, Re 1.80%~2.50%, Si 0.25%~0.35%, C≤0.04%, Fe≤0.20%, Mn≤0.15%, Zr≤0.10%, P≤0.018%, S≤0.001%, with the balance being Ni and unavoidable impurities.

[0037] Example 3 The preparation method according to Example 1 differs in that: S1: Cleaning temperature 40℃, AlCl3 accounts for 10% of the volume of the first reaction gas in the aluminization deposition, the first reaction gas flow rate is 200L / h, the aluminization deposition temperature is 980℃, and the deposition time is 3.5h; SiCl4 accounts for 4% of the volume of the second reaction gas in the silicon deposition, the silicon deposition temperature is 900℃, and the deposition time is 1.5h. S2: The furnace temperature in the low-pressure section is 650℃, the furnace temperature in the medium-pressure section is 950℃, the furnace temperature in the high-pressure section is 1050℃, and the diffusion heat preservation time is 3.5h; S3: The pressure reduction rate is 15Pa / min, the furnace pressure is reduced to 150Pa, the average temperature of the blades when pushed into the guide rail is 850℃, and the cooling rate is 2.5℃ / min. S4: The cooling rate is 3℃ / min, and the average blade temperature at the end of cooling is 500℃. S5: Maintain the third temperature distribution time for 10 minutes, the argon flow rate after heating is stopped is 90 L / h, maintain the furnace pressure at 1000 Pa, and the argon flow rate at the pressure is 40 L / h. All other steps are the same.

[0038] The prepared turbine blades contain the following chemical elements in the following proportions: Co 8.50%~9.50%, Cr 3.80%~4.80%, W 7.00%~9.00%, Mo 1.50%~2.50%, Al 6.40%~6.80%, Ta 6.00%~7.00%, Re 1.80%~2.50%, Si 0.40%~0.80%, C≤0.04%, Fe≤0.20%, Mn≤0.15%, Zr≤0.10%, P≤0.018%, S≤0.001%, with the balance being Ni and unavoidable impurities.

[0039] Example 4 The preparation method according to Example 1 differs in that: S1: Replace the DD6 single-crystal nickel-based high-temperature alloy turbine blades with DD402 single-crystal nickel-based high-temperature alloy turbine blades; the remaining steps are the same.

[0040] The prepared turbine blades contain the following chemical elements in the following proportions: Co 5.00%~6.00%, Cr 8.00%~9.00%, W 7.60%~8.40%, Mo 2.50%~3.50%, Al 6.00%~6.80%, Ti 1.00%~1.50%, Nb 0.50%~1.00%, Ta 5.80%~6.20%, Si 0.15%~0.35%, C≤0.01%, Zr≤0.01%, with the balance being Ni and unavoidable impurities.

[0041] Example 5 The preparation method according to Example 1 differs in that: S2: Replace the alumina gasket with a zirconia gasket; the remaining steps are the same.

[0042] The prepared turbine blades contain the following proportions of chemical elements: Co 8.50%~9.50%, Cr 3.80%~4.80%, W 7.00%~9.00%, Mo 1.50%~2.50%, Al 6.10%~6.40%, Ta 6.00%~7.00%, Re 1.80%~2.50%, Si 0.30%~0.50%, C≤0.04%, Fe≤0.20%, Mn≤0.15%, Zr≤0.10%, P≤0.018%, S≤0.001%, with the balance being Ni and unavoidable impurities.

[0043] Example 6 The preparation method according to Example 1 differs in that: S1: Replace the DD6 single-crystal nickel-based high-temperature alloy turbine blades with DD432 single-crystal nickel-based high-temperature alloy turbine blades; the remaining steps are the same.

[0044] The prepared turbine blades contain the following chemical elements in the following proportions: Co 8.00%~10.00%, Cr 4.30%~5.60%, W 7.70%~9.50%, Mo 0.80%~1.40%, Al 6.00%~7.30%, Ti 0.50%~1.50%, Ta 6.00%~8.00%, Re 2.50%~4.00%, Hf 0.05%~0.15%, Si 0.40%~0.60%, C≤0.01%, with the balance being Ni and unavoidable impurities.

[0045] Example 7 The preparation method according to Example 1 differs in that: S2: Replace the alumina gasket with a yttrium oxide gasket; the remaining steps are the same.

[0046] The prepared turbine blades contain the following proportions of chemical elements: Co 8.50%~9.50%, Cr 3.80%~4.80%, W 7.00%~9.00%, Mo 1.50%~2.50%, Al 6.10%~6.40%, Ta 6.00%~7.00%, Re 1.80%~2.50%, Si 0.30%~0.50%, C≤0.04%, Fe≤0.20%, Mn≤0.15%, Zr≤0.10%, P≤0.018%, S≤0.001%, with the balance being Ni and unavoidable impurities.

[0047] Comparative Example 1 The preparation method according to Example 1 differs in that: S3: Change the second temperature distribution to ensure that the leaf tip temperature is still 35±3℃ higher than the leaf root temperature, and the rest of the steps are the same.

[0048] Comparative Example 2 The preparation method according to Example 1 differs in that: S5: Change the third temperature distribution to ensure that the leaf root temperature is still 35±3℃ higher than the leaf tip temperature, and the rest of the steps are the same.

[0049] Comparative Example 3 The preparation method according to Example 1 differs in that: S2: Cancel segmented pressure control and heating. After closing the furnace door and evacuating the furnace, directly fill the furnace with argon gas to maintain the pressure inside the furnace at 500Pa and raise the temperature to 1020℃. The remaining steps are the same.

[0050] Comparative Example 4 The preparation method according to Example 1 differs in that: S2: After the furnace temperature is raised to 1020℃, the pressure is immediately reduced and the first temperature distribution is switched. No diffusion insulation is performed. The remaining steps are the same.

[0051] Comparative Example 5 The preparation method according to Example 1 differs in that: S3 and S5: Eliminate the temperature difference between the leaf root and leaf tip in the first, second, and third temperature distributions, and ensure that the temperature in each zone is 1020℃ during S2 diffusion insulation. All other steps are the same.

[0052] Experimental Example 1 Metallographic samples were taken from the blade sections of the blades prepared in Examples 1-7 and Comparative Examples 1-5. After mounting, grinding, and polishing, indentation tests were performed using an instrumented nanoindentation testing apparatus with a Berkovich diamond indenter. The maximum indentation depth was controlled within 1 / 10 of the diffusion layer thickness but not exceeding 200 nm. The loading rate was 10 nm / s, the holding time was 10 s, and the unloading rate was 10 nm / s. For each sample, a test point was selected at 10 μm intervals from the surface towards the substrate on the diffusion layer section. Five effective indentation tests were performed at each test point, and the average value was taken. The indentation hardness and indentation modulus were calculated from the load-displacement curve according to the Oliver-Pharr method until the hardness value stabilized within the hardness range of the substrate. The arithmetic mean of the indentation hardness of all measured test points was taken as the nanoindentation hardness value of the sample.

[0053] Metallographic samples were taken from the blade body of the blades prepared in Examples 1-7 and Comparative Examples 1-5. After mounting, grinding, and polishing, the samples were electrolytically etched with a 5% oxalic acid aqueous solution at a voltage of 5V for 5-10s. The samples were observed under an optical microscope at 500x magnification. The depth of the diffusion layer was measured from the blade surface along a direction perpendicular to the surface to the boundary line between the diffusion layer and the substrate using an eyepiece micrometer. Each division on the eyepiece micrometer corresponds to a fixed length. The diffusion layer depth value of the field of view was calculated. Five fields of view were measured in a continuous area of ​​the diffusion layer for each sample, and the arithmetic mean was taken as the diffusion layer depth of the sample.

[0054] Table 1. Nanoindentation hardness and diffusion layer depth of the examples and comparative samples ; As can be seen from Table 1, the nano-indentation hardness and diffusion layer depth of the sample in the example are significantly better than those in the comparative example, indicating that the segmented pressure-controlled diffusion heat treatment process of the present invention can effectively promote the inward diffusion of Al and Si elements and form a dense, continuous and uniformly thick silicon-aluminate diffusion layer.

[0055] In Comparative Example 1, the second temperature distribution was changed to be higher at the blade tip than at the blade root in stage S3, which is equivalent to canceling the first temperature difference reversal. During the cooling process, the longitudinal temperature difference direction remained unchanged, and the differential thermal strain continued to accumulate in the same direction. A uniaxial stress field was formed in the diffusion layer. The precipitation of the β-NiAl phase was restricted in the uniaxial tensile stress field and the density decreased. At the same time, the stress concentration area hindered the further inward diffusion of Al and Si. Therefore, the hardness and depth were significantly lower than those of the Example.

[0056] In Comparative Example 2, the third temperature distribution was changed to be higher at the leaf root than at the leaf tip in stage S5, which is equivalent to canceling the second temperature reversal. The final stress direction adjustment was not performed in the low temperature range, and the residual stress in the diffusion layer was not released in reverse before the material hardened. The β-NiAl phase lattice distortion was retained to room temperature. Since the first reversal in stage S3 was performed normally, the diffusion conditions were basically the same as in Example 1, so the depth was close to the level of Example 1.

[0057] Comparative Example 3 eliminated the S2 segmented pressure control heating and directly heated to 1020℃ with a single pressure of 500Pa. Insufficient degassing in the low-pressure section caused residual chlorides to corrode the blade surface at high temperature, hindering the diffusion of Al and Si inward. Poor temperature uniformity in the medium-pressure section caused fluctuations in the diffusion layer thickness. Insufficient thermal balance in the high-pressure section led to a decrease in diffusion driving force. Under the combined effect, both hardness and depth were significantly lower.

[0058] Comparative Example 4, with the S2 stage of diffusion insulation at 1020℃ cancelled, showed that Al and Si in the preform did not obtain sufficient thermal activation energy to migrate into the matrix, but only remained on the surface to form an extremely thin enriched layer. The β-NiAl phase was almost not formed, the hardness was close to that of the matrix, and the depth was only an extremely thin surface adhesion layer, making it the worst performing sample among all samples.

[0059] Comparative Example 5 eliminated the longitudinal temperature gradient throughout S2 to S5. During the diffusion insulation stage, there was no temperature difference, i.e., no pre-establishment of the thickness slope. During the cooling stage, there was no temperature difference, i.e., no differential thermal strain reversal control. Although β-NiAl phase still precipitated in a single temperature field, the lack of a temperature difference-driven stress release and reverse accumulation mechanism resulted in lower hardness and depth than all other examples.

[0060] Experimental Example 2 Test points were selected on the surfaces of the blades prepared in Examples 1-7 and Comparative Examples 1-5. X-ray diffraction residual stress analyzer was used with Cu target Kα radiation, and the diffraction crystal plane was the β-NiAl phase (211) crystal plane. 2 The ψ method measures the ψ angle at four angles: 0°, 15°, 30°, and 45°. The instrument automatically calculates and displays the residual stress values ​​σ1 and σ2, as well as the corresponding principal stress direction angles θ1 and θ2. In the residual stress values ​​σ1 and σ2, "+" indicates tensile stress, and "-" indicates compressive stress.

[0061] Rectangular samples of 10mm×10mm×3mm were cut from the blades prepared in Examples 1-7 and Comparative Examples 1-5 and placed in a box-type resistance furnace heated to 1050℃±10℃. After holding at this temperature for 10 minutes, the samples were removed and immersed in water at 25℃±5℃ for 5 seconds to cool. Each cycle was completed by removing the samples and drying them. After every 10 cycles, the surface of the samples was examined with a 20x magnifying glass. The number of cycles at which the first visible crack or peeling appeared was recorded to evaluate the thermal shock resistance of the sample's diffusion layer.

[0062] Table 2 Service performance of the examples and comparative samples ; As can be seen from Table 2, the σ1 and σ2 of the example samples are both compressive stresses with large absolute values, and the number of thermal shock cycles is significantly higher than that of the comparative sample. This indicates that the segmented pressure-controlled diffusion heat treatment process of the present invention can effectively establish a compressive stress state in the diffusion layer and suppress crack initiation through two temperature difference reversals and gradual stress regulation.

[0063] Comparative Example 1 eliminates the first temperature reversal. During the cooling process, the direction of differential thermal strain remains unchanged, the contraction sequence of the blade tip and the blade root does not reverse, the thermal mismatch strain continues to accumulate in the same direction, a uniaxial tensile stress field is formed in the diffuser layer, the compressive stress loses its closing effect on microcracks, the surface microcracks expand rapidly during thermal cycling, and the thermal shock cycle resistance is poor.

[0064] Comparative Example 2 cancels the second temperature reversal. The final stress direction adjustment was not performed in the low-temperature range, and the residual differential thermal strain in the diffusion layer was not released in reverse before the material hardened. The β-NiAl phase lattice distortion was retained to room temperature, and the residual stress was tensile stress. Since the first reversal in stage S3 was performed normally, the stress was released and accumulated in reverse once. The tensile stress amplitude was less than that in Comparative Example 1, and the number of cycles was higher than that in Comparative Example 1 but lower than that in all examples.

[0065] Comparative Example 3: When the S2 segmented pressure control heating was cancelled, residual chloride corroded the blade surface at high temperature, and local stress concentration sources were formed in the diffusion layer. At the same time, insufficient temperature uniformity caused the diffusion layer thickness to fluctuate, the stress distribution to be disordered, and finally residual tensile stress was formed, resulting in extremely poor thermal shock cycle resistance.

[0066] Comparative Example 4, with S2 diffusion insulation removed, shows that Al and Si in the prefabricated layer did not migrate into the matrix, the β-NiAl phase was almost not formed, and the extremely thin enriched layer lacked stress-bearing capacity. The blade surface was exposed or semi-exposed, and the residual stress test value reflected the thin layer state of the matrix surface. Due to the lack of diffusion layer protection, the matrix was directly exposed to the oxidizing environment during thermal cycling, resulting in the lowest thermal shock cycling performance among all samples.

[0067] Comparative Example 5 completely eliminated the longitudinal temperature gradient. Although a β-NiAl phase diffusion layer was formed in a single temperature field and the residual stress still exhibited compressive stress, it lacked differential thermal strain reversal control driven by temperature difference. The compressive stress amplitude was much smaller than in all embodiments, resulting in insufficient ability to suppress microcracks and poor resistance to thermal shock cycles.

[0068] Experimental Example 3 Take the blade prepared in Example 1, and cut small sample pieces containing the complete coating cross-section from the leaf root, leaf middle and leaf tip regions respectively. Use epoxy resin cold mounting method to embed and fix the sample, ensuring that the coating cross-section is parallel to the bottom surface of the mounting block so as to ensure that the subsequent observation direction is perpendicular to the coating interface. Subsequently, the cross-section was progressively ground using 180#, 400#, 800#, 1200#, and 2000# silicon carbide wet sandpaper. Each time a grade of sandpaper was changed, the sample was rotated 90° to remove the previous scratches. Water cooling was continuously applied during the grinding process to prevent heat damage to the coating. After grinding, W2.5 and W1.0 diamond polishing agents were used in conjunction with a polishing cloth for mechanical polishing until the cross-section reached a mirror finish and was free of visible scratches. The sample was then ultrasonically cleaned in anhydrous ethanol for 5 minutes, removed, and dried with high-purity nitrogen. The observation surface of the sample was then subjected to ion sputtering gold spraying, with a gold thickness of approximately 15 nm. The prepared sample was placed on the scanning electron microscope stage, the accelerating voltage was set to 20 kV, and backscattered electron imaging mode was selected to observe the morphology of the coating cross-section at the leaf root, leaf midsection, and leaf tip. The observation results are as follows: Figure 1 As shown.

[0069] Figure 1 Figure a shows the cross-sectional morphology of the leaf root. It can be seen that the coating at the leaf root consists of a dense and flat proliferating layer on the surface and an interdiffusion zone below. The layer interface is clear and straight. A large number of fine, bright white high atomic number precipitates are diffusely distributed in the interdiffusion zone. The matrix is ​​a homogeneous single-crystal nickel-based alloy without interface cracks or pore defects. Moreover, since the root temperature is lower than that at the leaf tip during the diffusion insulation stage, the diffusion driving force of Al and Si elements is relatively weak, the thickness of the interdiffusion zone is at a low level, and the degree of element interdiffusion is mild. Combined with the segmented pressure-controlled degassing and the root compressive stress effect of the bimetallic clamp, the coating and matrix interface are densely bonded, and the residual compressive stress state effectively inhibits the initiation of microcracks in the brittle coating.

[0070] Figure 1b is a cross-sectional morphology diagram of the leaf, which shows that the proliferating layer is continuous and complete. The thickness of the interdiffusion zone is increased compared with that of the leaf root. The interface with the matrix has a wavy metallurgical bonding morphology. The high atomic number precipitates in the interdiffusion zone are smaller in size and more uniformly distributed. A clear element diffusion influence zone is visible on the matrix side. The temperature in the middle region during diffusion insulation is between that of the root and the leaf tip. The element interdiffusion rate is moderate, forming a transition gradient of coating thickness along the leaf height direction. The segmented pressurization process environment ensures the uniformity of the diffusion process in this region. The stress redistribution effect of subsequent temperature reversal results in no obvious stress concentration defects at the interface, and the coating structure has good integrity.

[0071] Figure 1 c is a cross-sectional morphology diagram of the blade tip. The proliferating layer is uniform and continuous, and the thickness of the interdiffusion zone is significantly greater than that of the root and middle parts. There is no clear straight interface between the interdiffusion zone and the matrix, showing a gradual metallurgical transition characteristic. The precipitated phase in the interdiffusion zone extends into the matrix in a fine needle-like network. Diffusion-induced precipitated phases are also diffusely distributed in the matrix. The blade tip is in the highest temperature region during the diffusion heat preservation stage. The higher temperature significantly increases the diffusion coefficient of Al and Si atoms. The deep diffusion of elements forms a thicker interdiffusion layer. At the same time, the stress regulation mechanism of two temperature difference reversals effectively offsets the shrinkage stress of the thick coating, so that the interface bonding under the thick diffusion layer is still maintained, without coating peeling and macroscopic cracks.

[0072] Experiment Example 4 A sample containing a complete coated section was taken from the middle part of the blade prepared in Example 1. It was then fixed using a vacuum cold-mounting method with low-shrinkage epoxy resin. The sample was subsequently ground stepwise with silicon carbide sandpaper, then polished with diamond suspension and colloidal silica until a mirror-like, scratch-free finish was achieved. After ultrasonic cleaning with anhydrous ethanol and drying with high-purity nitrogen, the sample underwent carbon vapor deposition for conductivity. The carbon film thickness was controlled to be 8-15 nm. The sample was then placed on the sample stage of an electron probe microanalyzer, with an accelerating voltage of 15 kV, a main element test beam current of 20 nA, and a trace element test beam current of 50 nA for O and Cl. The spot size was 1 μm. Corresponding spectroscopic crystals were used to collect elemental signals of Al, Si, Ni, Co, Cr, O, and Cl. A linear scanning array was arranged along the normal direction perpendicular to the coating surface, with a scanning depth range of 0–100 μm and a step size of 1 μm. The residence time for major elements was 0.2–0.5 s / point, and the residence time for O and Cl was 1 s / point. Calibration was performed using pure elemental standards. After ZAF quantitative correction, the mass fraction variation curves of each element along the depth direction were obtained. Background signals were simultaneously acquired to determine the method detection limits for O and Cl. The detection results are as follows: Figure 2 As shown.

[0073] from Figure 2As can be seen from the data, in the leaf samples prepared in Example 1, the Al element maintains a high content plateau in the surface proliferation zone of 0~20μm, and decreases monotonically with increasing distance from the surface, falling back to the intrinsic Al content of the DD6 matrix at a depth of 100μm. This corresponds to the process of Al atoms continuously migrating into the matrix during the high-temperature diffusion stage after aluminization deposition. The Si element forms a significant enrichment peak in the near-surface 0~10μm range, then decreases rapidly, and maintains a low content stable state after a depth of 20μm, reflecting the distribution characteristics that the Si atom diffusion rate is lower than that of Al, and that after silicon-containing deposition and diffusion, it is mainly retained on the outer side of the coating. The Ni element content gradually increases from the surface to the interior, forming a mixture with the Al element. The complementary concentration gradients directly reflect the metallurgical behavior of Ni diffusing outward and forming interdiffusion couples with Al diffusing inward. Co and Cr elements increase slowly with depth and tend to stabilize in the matrix region, corresponding to the reverse diffusion migration of alloying elements in the matrix. O and Cl elements remain at extremely low levels throughout the process, close to the method detection limit, proving that the low-pressure degassing and vacuum diffusion environment in the process effectively eliminates residual chlorides and avoids high-temperature oxidation. The coating interface is clean and free of continuous oxide layers and harmful impurity enrichment. The overall composition curve is continuous and smooth without abrupt changes, indicating that the segmented pressure-increasing and heat-preserving diffusion heat treatment fully drives element interdiffusion, and the coating and the matrix form a good metallurgical bond with uniform transition.

[0074] Experimental Example 5 The blade sample prepared in Example 1 is designated as H1, and the blade samples prepared in Comparative Examples 1-5 are designated as C1-C5, respectively. For the blade samples prepared in H1 and C1-C5, a flat sample of approximately 10mm × 10mm × 3mm was cut from the middle of the blade, retaining the original coating surface. The test surface was kept in its original coating state without grinding, polishing, or etching. It was only gently ultrasonically cleaned with analytical grade ethanol for 1-2 minutes to remove loose surface contaminants. After drying with high-purity nitrogen, it was fixed on a zero-background silicon sample stage. The sample height was adjusted so that the test surface was aligned with the center of the goniometer. A Cu-... Phase characterization was performed using an X-ray diffractometer with a Kα radiation source. The tube voltage was set to 40 kV and the tube current to 40 mA. A parallel grazing incidence mode with an incident angle of 2° was selected. The scanning range was set to 2θ = 20°–90°, with a step size of 0.02° and a counting time of 0.5–1.0 s per step. After testing, the original spectra were subjected to background subtraction and Kα2 stripping. A pseudo-Voigt function was used for peak fitting and phase assignment. Each group of spectra was normalized individually and then stacked vertically in a staggered manner to compare the differences in phase composition and crystallization characteristics of coatings under different processes. The test results are as follows: Figure 3 As shown.

[0075] from Figure 3As can be seen from the data, the characteristic diffraction peaks (100), (110), (200), and (211) of the β-NiAl phase in sample H1 are sharp and have the highest intensity. This indicates that after segmented pressure-controlled heating and sufficient diffusion at 1020℃, a highly crystalline, continuous, and dense ordered β-NiAl phase was formed in the coating, and the Al element and the nickel-based alloy matrix fully interdiffused to complete the phase transformation. In sample C1, the first temperature reversal was canceled, and the superlattice characteristic peaks of β-NiAl were significantly weakened, and the proportion of the ordered phase decreased. This is because the unidirectional continuous thermal stress accumulation inhibited the deep diffusion of Al element and the densification growth of the β phase, which is consistent with the pattern of a significant decrease in the thickness of the diffusion layer.

[0076] The second low-temperature thermo-reversal of sample C2 was cancelled. Its β-NiAl peak position was consistent with that of H1, but the peak intensity was slightly reduced and the peak width was slightly increased. This indicates that the second thermo-reversal mainly regulates the low-temperature residual stress and lattice distortion, and has little effect on the type and overall content of the phase. The diffraction peak broadening is only due to the insufficient release of lattice strain.

[0077] The C3 sample, after canceling the segmented pressure-controlled heating process, showed extremely low intensity of the β-NiAl diffraction peak and significant baseline background fluctuations. This was due to insufficient degassing under low pressure, which led to residual chloride corrosion of the interface and poor heat transfer uniformity. This not only hindered the full formation of the β phase but also introduced background noise caused by interface contamination and oxidation.

[0078] The C4 sample, without the high-temperature diffusion insulation step, showed that the spectrum was dominated by the characteristic diffraction peaks of the γ-Ni matrix, while the signal of the β-NiAl phase was so weak as to be close to the detection limit. This indicates that without high-temperature thermal activation conditions, the Al in the preform layer cannot undergo sufficient interdiffusion reaction with the matrix to form a stable β-NiAl phase, and only a very thin element-enriched layer exists on the surface. This shows that high-temperature diffusion insulation is a core and necessary process for forming the target aluminide coating phase.

[0079] The C5 sample had its longitudinal temperature gradient eliminated throughout the process. The intensity of the β-NiAl characteristic peak was moderate, and the diffraction contribution of the γ-Ni matrix was relatively enhanced. This corresponds to a reduction in the thickness of the diffusion layer without temperature difference control, making it easier for X-rays to penetrate the coating and reach the matrix. This confirms that the longitudinal temperature difference can pre-adjust the thickness of the diffusion layer and increase the proportion of the β phase on the surface.

[0080] In summary, segmented pressure control and diffusion insulation determine the degree of β-NiAl phase formation and coating thickness, while the two temperature reversals mainly regulate the lattice stress state and have a weaker impact on phase composition than the diffusion process parameters.

Claims

1. A segmented pressure-controlled diffusion heat treatment method for chemical vapor deposition of silicon-containing aluminizing in high-temperature alloy turbine blades, characterized in that, Includes the following steps: S1: The nickel-based high-temperature alloy turbine blades are cleaned and the air film pores are ventilated. Non-permeable parts are shielded with an alumina sleeve. After being loaded into the vapor deposition furnace, the first reaction gas containing AlCl3 is introduced under a protective atmosphere for aluminization deposition, and then the second reaction gas containing SiCl4 is introduced for silicon deposition. The reaction tail gas is treated by alkaline absorption and a leakage interlock is set. After the deposition is completed, the gas is switched to argon purging and cooling to obtain a blade with a silicon-aluminate pre-layer on the surface. S2: The blade root with the pre-made layer is inserted into the bimetallic thermal expansion locking clamp using an alumina isolation pad, clamping only the blade root and keeping the blade body and tip free. The product blade and the control blade with temperature measuring points at the blade root, blade middle and blade tip are placed together in a multi-zone heating vacuum furnace. The furnace has 6 independent heating zones along the blade height. After evacuation, the furnace pressure is controlled and the temperature is raised to the corresponding diffusion temperature in the vacuum low pressure zone, 50Pa medium pressure zone and 500Pa high pressure zone. Finally, the temperature is held. During the holding period, the output of each zone is continuously adjusted according to the measured temperature of the three measuring points of the control blade to keep the blade tip temperature higher than the blade root. S3: After the heat preservation is completed, adjust the furnace pressure to the cooling pressure, reduce the set temperature of the independent heating zone at the preset cooling rate, and keep the actual temperature of the blade tip higher than the actual temperature of the blade root. When the average temperature of the blade enters the first reversal temperature window, smoothly reverse the axial temperature difference direction within 5 minutes so that the actual temperature of the blade root is higher than the actual temperature of the blade tip. S4: Continue cooling while keeping the measured temperature at the blade root higher than that at the blade tip. During the cooling process, continuously adjust the output of each heating zone based on the measured temperatures at the blade root, blade middle, and blade tip to maintain the axial temperature difference until the average temperature of the blade drops to the preset end temperature. S5: When the average temperature of the blade drops to the second reversal temperature window, within 5 minutes, smoothly reverse the axial temperature difference direction from the blade root being higher than the blade tip to the blade tip being higher than the blade root, and maintain this for a preset time. Then, gradually reduce the temperature difference to zero and stop heating. At the same time, argon gas is introduced and the furnace pressure is maintained. The furnace door is kept closed until the blade temperature drops below the set temperature, at which point the furnace door is opened and the blade is removed.

2. The segmented pressure-controlled diffusion heat treatment method for chemical vapor deposition of silicon-containing aluminizing in high-temperature alloy turbine blades according to claim 1, characterized in that: The nickel-based superalloy turbine blade described in S1 is one of the following: DD6 single-crystal nickel-based superalloy turbine blade, DD402 single-crystal nickel-based superalloy turbine blade, and DD432 single-crystal nickel-based superalloy turbine blade.

3. The segmented pressure-controlled diffusion heat treatment method for chemical vapor deposition of silicon-containing aluminizing in high-temperature alloy turbine blades according to claim 1, characterized in that: The cleaning temperature in S1 is 25~40℃; the volume ratio of AlCl3 in the first reaction gas is 6%~10%, and the gas flow rate of the first reaction gas is 160L / h~200L / h; the aluminization deposition temperature is 930~980℃, and the deposition time is 2.5~3.5h; the volume ratio of SiCl4 in the second reaction gas is 1%~4%; the silicon deposition temperature is 865~900℃, and the deposition time is 0.8~1.5h.

4. The segmented pressure-controlled diffusion heat treatment method for chemical vapor deposition of silicon-containing aluminizing in high-temperature alloy turbine blades according to claim 1, characterized in that: The isolation gasket mentioned in S2 is one of the following: alumina gasket, zirconium oxide gasket, and yttrium oxide gasket.

5. The segmented pressure-controlled diffusion heat treatment method for chemical vapor deposition of silicon-containing aluminizing in high-temperature alloy turbine blades according to claim 1, characterized in that: The diffusion temperature of the vacuum low-pressure section in S2 is 580~650℃; the diffusion temperature of the 50Pa medium-pressure section is 860~950℃; the diffusion temperature of the 500Pa high-pressure section is 1000~1050℃; and the heat preservation time is 2.5~3.5h.

6. The segmented pressure-controlled diffusion heat treatment method for chemical vapor deposition of silicon-containing aluminizing in high-temperature alloy turbine blades according to claim 1, characterized in that: The furnace pressure in S3 is adjusted by reducing the pressure at a rate of 8~15 Pa / min; the cooling pressure is 100~150 Pa; the average temperature of the blades is 800~850℃; and the cooling rate is 1~2.5℃ / min.

7. The segmented pressure-controlled diffusion heat treatment method for chemical vapor deposition of silicon-containing aluminizing in high-temperature alloy turbine blades according to claim 1, characterized in that: The cooling rate described in S4 is 1~3℃ / min; the preset end temperature is 450~500℃.

8. The segmented pressure-controlled diffusion heat treatment method for chemical vapor deposition of silicon-containing aluminizing in high-temperature alloy turbine blades according to claim 1, characterized in that: The preset time in S5 is 5~10 min; the argon gas flow rate is 60~90 L / h; the furnace pressure is maintained at 700~1000 Pa, and the argon gas flow rate at the pressure is 25~40 L / h.

9. A high-temperature alloy turbine blade prepared by a segmented pressure-controlled diffusion heat treatment method for chemical vapor deposition of silicon-containing aluminizing as described in any one of claims 1 to 8, characterized in that: The blade comprises the following chemical elemental components by mass percentage: Co 5.00%~6.00% or 8.00%~10.00% Cr 3.80%~5.60% or 8.00%~9.00% W 7.00%~9.50%、 Mo 0.80%~1.40% or 1.50%~3.50%, Al 5.90%~6.80%、 Ta 5.80%~8.00%, Re 0% or 1.80%~4.00%, Si 0.15%~0.80%, Ti 0 or 0.50%~1.50%, Nb 0 or 0.50%~1.00%, Hf 0 or 0.05%~0.15%, C≤0.04%, Fe≤0.20%, Mn≤0.15%, Zr≤0.10%, P≤0.018%, S≤0.001%, with the balance being Ni and unavoidable impurities.

10. The application of the high-temperature alloy turbine blade prepared by the segmented pressure-controlled diffusion heat treatment method of chemical vapor deposition of silicon-containing aluminizing as described in claim 9, characterized in that: The blades can be used in the fields of high-pressure turbine blades for aero-engines, hot-end components of industrial heavy-duty gas turbines, and guide blades for marine gas turbines. Their nano-indentation hardness is >7GPa and their thermal shock resistance cycle count is >200 cycles.

Citation Information

Patent Citations

  • Gas phase aluminizing method for nickel-based single crystal superalloy turbine blade

    CN122189558A